Efek Perendaman Ikan Asin Sepat dalam Cuka Makan terhadap Penurunan Kadar Formalin - Abdurraafi’ Maududi Dermawan; Dwi Haryadi; Fath Dwisari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
There are still many salted fish producers or sellers who misuse formalin to preserve salted fish. Because of its easy availability and can extend shelf life, this chemical is often misused as a food preservative, and its carcinogenic nature the use of formalin in food can have a negative impact on health. Various efforts and previous studies have been carried out to deformalize and reduce formalin levels in food, one of which is through the use of table vinegar in reducing the formalin content of Salted Sepat Fish. The study aims to determine the effect of soaking in vinegar solution to reduce the formalin content in Salted Sepat Fish and determine the concentration of vinegar solution that is effective in reducing formalin levels in Salted Sepat Fish. The study was conducted as a true experimental research with Pre and Post Test Control Group research design. Samples of Salted Sepat Fish used in this study were obtained from several traditional markets in Pontianak City (Flamboyan Market, Tengah Market, Dahlia Market, Teratai Market and Kemuning Market). The results showed that there was a decrease the concentration of formalin after soaking with 25% dining vinegar solution at 6%, 8% and 10% concentration variations with a percentage decrease of 23.32%; 50.77% and 68.21% respectively. The solution of table vinegar with a concentration of 8% was the most effective in reducing formalin levels in Salted Sepat Fish.